Children of the Earth. no.12 (Lammas, 1984) - (:unkn) unknown (Children of the Earth, 1984)
Hello Again -- Announcements -- Book Review: The Continuum Concept by Jean Liedloff / reviewed by Ertha -- Children in Pagan Communities #2 / by Morag na Bienne -- Miscellany -- Kitchen Witchery: Sabbat Cakes ; Nest Eggs / recipes by Windsinger -- Letters -- Soap Crayons / recipe by Windsinger -- Healing / healing chant by Morgan & Janel -- The Grasshopper and the Lion / by Morg na Bienne -- Pen Pals
1 Electronic record(s). 5242758 bytes. 11 pages. CotE_v04n12_1984.pdf
Keywords: Children of the Earth (Newsletter); Neopagan families; Child rearing--Religious aspects--Neopaganism; Child rearing--Religious aspects--Wicca; Neopagan children--Education; Pregnancy--Religious aspects; Liedloff, Jean. Continuum concept; Children's writings; Children's literature; Sabbat cakes--Recipes; Cooking (Eggs)--Recipes; Crayons--Recipes; Chants--Texts; Short stories; Recipes; Newsletters